Construção de instrumento sistematizado de enfermagem para near miss materno - Santos, Leila Cristina Oliveira (2021)
Introduction: Maternal near miss is defined by the World Health Organization as the woman who almost died, but survived serious complications during pregnancy, childbirth or up to 42 days after the end of pregnancy. It constitutes an important marker of health and obstetric quality and gathers a set of diagnostic criteria that identify the potentially threatening conditions to the woman's life, which requires priority in attendance, so that she receives adequate attention, care and support and not evolve to the outcome of maternal death. The care directed to women, based on health technologies, is one of the points proposed to obtain more security in care. In this sense, the study deals with the implementation of a light-hard technology for structuring assistance to maternal near miss. Objectives: To build a systematic nursing instrument for use in assisting women in maternal near miss, based on CIPE ®. Method: This is a methodological study, which was carried out in two phases: Analysis of the concept of maternal near miss and Elaboration of the research instrument. In the analysis and synthesis of the selected articles, the identified data were transcribed, categorized and stored in a Microsoft Office Excel® spreadsheet and the results were discussed in a descriptive manner. Results: The findings were categorized into Events / Health Situations Associated with Near Miss Materno and Concept Analysis of Near Miss Materno, whose data supported the construction of the research instrument. Conclusion: the study made it possible to clarify the concept of Near Miss Materno, demystifying the idea that it is only a population-based survey for the analysis of maternal morbidity. It allowed to define it operationally as a feasible phenomenon, which can be observed and monitored by nursing. It is expected, therefore, that it can contribute to the practice of assistance provided by the Nursing Process, in addition to becoming a guiding object in professionals' decision-making, improving maternal care.